Optimizing organic amendment applications to enhance carbon sequestration and economic benefits in an infertile sandy soil. (1st February 2022) - Xu, Cong; Wang, Jidong; Wu, Di; Li, Chuanzhe; Wang, Lei; Ji, Cheng; Zhang, Yongchun; Ai, Yuchun
Abstract: A thorough understanding of the agricultural, ecological, and economic benefits of organic amendment (OA) application in infertile soils is crucial for facilitating agricultural sustainability. We conducted a three-year field study to evaluate the effects of OA application on soil organic carbon (SOC) sequestration, crop yields, and the net ecosystem economic benefit (NEEB) in a typical infertile sandy soil (with an initial SOC content of 2.56 g kg −1 ) of the ancient Yellow River alluvial plain. In addition to the control (CK; non-OA application), two types of OAs, namely, manure-based organic fertilizer (M) and spent mushroom residue (MR), were each applied at 12, 24, and 36 Mg ha −1 yr −1 . Two scenarios of OA application practices, namely, conventional manual OA application (AMA) and mechanical OA application (AME), were considered in the economic evaluation. An increase of 1 g kg −1 SOC content could improve the crop yield by 2.25 Mg ha −1 yr −1 . Compared with the CK, the application of OAs enhanced the SOC content and SOC stock by 14.6%–39.8% and 8.5%–28.2%, respectively. However, the SOC sequestration efficiency of the OAs tended to decrease under high rates of OA application. MR was observed to have greater potential than M in sequestering SOC and promoting soil aggregates. OA-induced SOC sequestration could neutralize 36.6%–97.8% of greenhouse gas emissions, which resulted in a reduction in the global warming potential and its cost by 0.62–2.68 Mg CO2 -eq ha −1 yr −1 and 15.46–65.78 CNY ha −1 yr −1, respectively. Nevertheless, in terms of the NEEB, the benefits of OA application on crop yield and SOC sequestration were largely offset by the increased material and labor costs. Compared with AMA, AME could save 10%–27% of agricultural costs. The AME of MR at a rate of 24 Mg ha −1 yr −1 achieved the highest NEEB. The results of this study suggest that a strategy involving the appropriate OA, optimal application rate, and cheapest incorporation cost for a specific individual soil should be adopted to achieve a sustainable solution for promoting crop productivity, enhancing SOC sequestration, and ensuring farmer income in infertile farming regions. Graphical abstract: Image 1 Highlights: Organic amendments have substantial potential to improve crop yield and SOC. High rates of organic amendment application decreased SOC sequestration efficiency. The cost of using organic amendments offsets their benefit in saving GWP costs. Mechanical spreading increased net ecosystem economic benefit by saving labor cost.